Controversial Face of Europe in the Official Discourse of Georgia After Independence - Irakli Chkhaidze (CES Working Papers, 2017)
Since the dissolution of the Soviet Union independent country of Georgia was faced ultimate challenges both in internal as well as foreign political spheres. Leader of the national movement and the first president of the Republic Zviad Gamsakhurdia was found victim of international isolation. Pro-European course of Georgia is connected to the presidency of Eduard Shevardnadze, former foreign minister of the Soviet Union, whose political project was to push Georgia to full membership of Euro Atlantic organizations. These tendencies became even stronger since 2003, after the “Rose Revolution”, under the government of the third president of Georgia Mikheil Saakashvili. In parallel with achievements on the way of Euro Integration anti-Western feelings were gradually emerged and strengthened in the Georgian public discourse. The successes in the pro-European politics and attempts to ratify the European legislative and constitutional norms were accompanied with protests supported by some public and political figures. The paper aims at analysing controversial nature of the process of Georgia's European Integration with its under streams and flows what have been making the process complicated.
Keywords: 330; Georgia; Europe; Official Discourse; West; Independence